Seroprevalence of hepatitis B in adult population of a district of Cajamarca - Albán Fernández, Lucía (2021)
Introduction: Hepatitis B is a transmissible disease, it is estimated that globally more than two billion people in the world have been infected with hepatitis B virus, of which 350 million are chronic carriers of hepatitis B surface antigen, and this chronic infection causes cirrhosis and liver cancer. In Peru, hyperendemic zones have been detected in the country's jungle. Cajamarca is the third department with the highest rates of liver and bile duct cancer. Celendín is a district located in Cajamarca, which borders the jungle, and maintains a high contact with it for trade and tourism. There have been no previous studies of this virus in Cajamarca´s population. Objective: to determine if there is a high seroprevalence of the hepatitis B virus in the adult population of the Celendín-Cajamarca district, in 2018. Material and methods: a cross-sectional study was carried out in 404 inhabitants of the Celendín district: a venous blood sample was taken to search for hepatitis B surface antigen and antibody, both by ELISA technique, and a survey was applied which included sociodemographic factors and associated risk factors. Results: it was obtained that 1.24% (n=5) asymptomatic habitants were positive for the surface antigen of hepatitis B. The age over sixty five years was associated with the antigen positivity. 67.86% of the population included, do not have protective levels of antibodies against the hepatitis B virus, of which 10% even refer to being vaccinated. Conclusions: there is a low seroprevalence of the hepatitis B virus in the population of the district of Celendín-Cajamarca in 2018. More than half of the population does not have protection for this virus, many even when vaccinated.